2020
DOI: 10.1111/anu.13126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary microminerals in early weaning diets on growth, survival, mineral contents and gene expression in gilthead sea bream (Sparus aurata, L) larvae

Abstract: In previous studies, combined inclusion of Zn, Mn and Se in early weaning diets improved larval growth, but suggested a potential toxicity by one of these elements. The present study aimed to determine the effect of the single inclusion of Zn, Mn, Se or Cu, their combination (Control+) or their absence (Control−) on larval diets. At the end of the trial, survival was significantly (p < .05) lowest in fish fed C+ diet (17.16 ± 7% mean ± SD), followed by that of larvae fed Mn diet (21.91 ± 7%). The highest survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
1
8
2
Order By: Relevance
“…Therefore, our results seem to suggest that curcumin may modulate growth of gilthead seabream larvae, but the doses of inclusion might need to be adjusted. The results for DW and TL were slightly lower compared to previous observations reported in the literature for gilthead seabream at the same age [59][60][61]. These differences might be explained by the more extreme feeding plan used in the present study, with co-feeding from mouth-opening with substantial livefeed replacement.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Therefore, our results seem to suggest that curcumin may modulate growth of gilthead seabream larvae, but the doses of inclusion might need to be adjusted. The results for DW and TL were slightly lower compared to previous observations reported in the literature for gilthead seabream at the same age [59][60][61]. These differences might be explained by the more extreme feeding plan used in the present study, with co-feeding from mouth-opening with substantial livefeed replacement.…”
Section: Discussioncontrasting
confidence: 90%
“…Moreover, survival rate at the end of the experiment was 4-5-fold lower compared to previous experiments with gilthead seabream at mouth opening, reared at similar conditions [38,59]. The larvae survival when weaning is started at mouth opening is usually lower when compared to a late weaning in older larvae (16)(17)(18)(19)(20)(21)(22), that can vary between 11-56% [60][61][62]. However, it was similar among treatments, implying that curcumin supplementation had no effect on the observed survival rates.…”
Section: Discussionmentioning
confidence: 55%
“…To obtain different particle sizes (i.e., 500 µm, 250 µm, and 125 µm), the dried pellets were ground (Braun, Kronberg, Germany) and sieved (Filtra, Barcelona, Spain) [ 20 ]. The proximate composition of basal diet (control) was Protein—64.46%, Lipid—20.44%, Ash—7.27%, Moisture—9.78% [ 20 , 55 , 56 ] ( Table 1 and Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research show that increasing Zn levels up to 245 mg/kg in rotifer had no negative effects on larval fish survival and even using zinc supplementation up to 306 mg/kg did not affect fish larval growth (Eryalçın et al, 2020; Satoh et al, 2008; Yamamoto et al, 2013). Moreover, low levels of zinc in the diet (85–100 mg kg −1 ) and enriched rotifers (119–306 mg kg −1 ) did not affect the growth of fish larvae (Izquierdo et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the importance of Se and Zn as a key part of metalloenzymes in aquatic physiology (Eryalçın et al, 2020), oxidative stress (Betancor et al, 2012; Izquierdo et al, 2017; Pacitti et al, 2013; Saleh et al, 2014), ossification (Yamaguchi, 1998) and improvements in larval growth and survival (Satoh et al, 2008), information regarding mineral nutrition in marine fish larvae is very limited. Moreover, the availability of the minerals depends on their molecular form such as Izquierdo et al (2017) observed using different forms of minerals (inorganic, organic and nanoparticles) in fish larvae feeding.…”
Section: Discussionmentioning
confidence: 99%